ALTERNATIF TEKNIK PASSIVE COOLING YANG EFISIEN PADA RUANG AUDITORIUM GEDUNG B UNIVERSITAS ‘AISYIYAH YOGYAKARTA - Pujiyanti, Indah (Jurnal Arsitektur dan Perencanaan (JUARA), 2018)
Abstract: The title of this paper research result is “The Passive Cooling Alternatif Technique Which Is Efficient In Auditorium Room ‘Aisyiyah Yogyakarta University. The problem which is going to be discussed in this final assignment research is to find the passive cooling technique which is applicable and effective to thermal comfort aspect for auditorium room ‘Aisyiyah Yogyakarta University. The goal which is going to be achieved in this final assignment is to know the passive cooling technique which is applicableand effective to thermal comfort aspect for auditorium room ‘Aisyiyah Yogyakarta University.The research method is conducted by direct observation on sample. Then the research model is made according to observation result. Then, the research model was tested by ecotect software to measure the temperature made by each model. The data got from the measurement were analyzed for thermal quality.Based on the analysis result, it is known that temperature in auditorium room ‘Aisyiyah Yogyakarta University until 30 celcius and that is not recommendation for comfortable room. Passive cooling techniques which are applicable for auditorium room ‘Aisyiyah Yogyakarta University are ventilative cooling and mass effect cooling (single banked room). It is also known that the effective passive cooling technique is mix-ventilation type with ratio ventilation more than 1:6,79. It is also known that there is a relation between room volume percentages which is passed by air stream with its air temperature in the room.Keywords: passive cooling technique, applicable, effective, auditorium room, UNISA